Nutraceuticals and cancer - Sarkar, Fazlul H. (Springer Netherlands, 2012)
This book is about Nutraceuticals in cancer therapy, specifically targeted and Adjuvant therapy. It shows several approaches for possibly reducing systemic toxicity. This book illustrates the role of several dietary agents, collectively called nutraceuticals or natural agents in the prevention and/or treatment of human malignancies known to be mediated through alterations in multiple molecular targets. This book contains sixteen chapters which begin with historical perspective on the value of natural agents in the prevention of human malignancies followed by a series of current topics on multiple nutraceuticals targeting multiple cancers. This collection would likely be useful for bringing newer generations with broader perspectives in launching cutting-edge innovative molecular research, which would certainly help in designing targeted clinical trials in order to realize the dream of customize strategies for the prevention and/or treatment of human malignancies without causing any systemic toxicity. Moreover, the knowledge gained would allow novel utilization of nutraceuticals as adjunct to both conventional chemotherapy and radiation therapy in order to improve the overall quality of life and survival of patients diagnosed with cancers.